A new species and updates on Paravelia Breddin, 1898 (Hemiptera, Heteroptera, Veliidae) in Brazil - Evaldo Alves Joaquim; Juliana Mourão dos Santos Rodrigues; Felipe Ferraz Figueiredo Moreira; Leandro Lourenço Dumas (ZooKeys)
Paravelia Breddin, 1898 is the most speciose genus of the subfamily Veliinae (Hemiptera, Heteroptera, Gerromorpha, Veliidae). It has gone through revisions since the 1990s, with several species being transferred to other genera, and currently contains 46 species distributed from Mexico to Argentina, 35 of which occur in Brazil. Here, we describe P. intervalensis sp. nov. based on material obtained during an expedition carried out in 2023 in the Parque Estadual Intervales, state of São Paulo. The new species can be distinguished from congeners by the the following: body length between approximately 5.1–5.5 mm; head, thorax, and abdomen (except posterior margin of sternum VII) not covered by small black denticles; humeral angle not spinose; forewings without bubble-like structures, with a pair of elongated yellow maculae basally and a small, diamond-shaped, white macula apically; venter of abdomen not covered by punctations; male abdominal sternum VII without projections or lobes; male proctiger without conical process at base, without lateral projections approximately at middle of length; and male paramere with a dorsal notch. We also present new distribution records of P. luederwaldti Rodrigues & Moreira, 2016 and provide an updated key to the Paravelia recorded from Brazil. This study increases the number of species of Paravelia known in Brazil to 36.